2019
DOI: 10.1007/s11769-018-0983-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Changes of Arable Land Driven by Urbanization and Ecological Restoration in China

Abstract: Since the industrial revolution, human activities have both expanded and intensified across the globe resulting in accelerated land use change. Land use change driven by China's development has put pressure on the limited arable land resources, which has affected grain production. Competing land use interests are a potential threat to food security in China. Therefore, studying arable land use changes is critical for ensuring future food security and maintaining the sustainable development of arable land. Base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…Recent land use studies show that forest cover in this catchment occupies only 5% of the 285 total area (Wang et al, 2014), while the remaining is dominated by cropland or barren terrain. Using the ratios of autotrophic to heterotrophic soil respiration for forested and non-forested land suggested by Hanson et al (2000), Rh was estimated to be 183 g C m 2 year 1 or 554×10 10 g C year 1 in total.…”
Section: 2mentioning
confidence: 99%
“…Recent land use studies show that forest cover in this catchment occupies only 5% of the 285 total area (Wang et al, 2014), while the remaining is dominated by cropland or barren terrain. Using the ratios of autotrophic to heterotrophic soil respiration for forested and non-forested land suggested by Hanson et al (2000), Rh was estimated to be 183 g C m 2 year 1 or 554×10 10 g C year 1 in total.…”
Section: 2mentioning
confidence: 99%
“…The species is however strongly associated with agricultural wetlands and the decrease is rice cultivation in PR China is expected to have drastically impacted the species. The area used for rice agriculture decreased by 11% since 1980 ( [90,91] herein), and it can be expected to follow the same pattern over the following decades [90]) due to the decrease in water availability [92,93]. Borzée et al [33] found "only two populations of D. immaculatus [ .…”
Section: General Introduction and Threats To The Three Speciesmentioning
confidence: 92%
“…Yao and Chang [35] consider that energy construction is related to energy economy development, and the development of energy construction is key to ecological civilization development. In the studies on land management related to ecological civilization, soil-water protection and arable land management are considered to be two basic elements of agro-ecological civilization system [36]. Accordingly, Qiao and Wang [37] put forward a three-phase agro-ecological civilization system.…”
Section: Literature Reviewmentioning
confidence: 99%